PG52 The paediatric 'dental chair' anaesthetic emergency – simulation training. (10th November 2020) - Shah, Ashoke; Rowson, Mark; Harrison, Liam; Bidwai, Anita
Abstract : Introduction: From 2001, all dental anaesthetic procedures were moved into a hospital setting to improve patient safety 1 . The Merseycare and Bridgewater community dental teams have a collaboration with Whiston Hospital to provide paediatric anaesthesia for dental treatment. A dedicated paediatric dental chair, in an outpatient setting is used 2 . As it is an isolated site, all staff who regularly attend this unit are required to keep their Paediatric Life Support (PLS) knowledge up to date. Annual PLS scenarios are recommended. We performed an in situ paediatric simulation in the dental suite. There is little documented evidence to show routine use of in-situ simulation in paediatric dental chair anaesthesia. Methods: The simulation was performed on separate days for each trust, in the dental suite, using the paediatric sim-man. The scenario initially presented as stridor, with escalation to cardiac arrest, with the anaesthetic and dental team present. It was further attended by the paediatric team, the resuscitation officer and anaesthetic emergency team. A survey was taken pre and post intervention, focusing on confidence and knowledge of paediatric cardiac arrest management using five multiple choice questions. Results: All participants significantly improved their knowledge and confidence when dealing with a paediatric cardiac arrest, table 1 . 100% of the attendees surveyed either agreed or strongly agreed that the simulation, enhanced their understanding of their role and management of a paediatric cardiac arrest and was a valuable learning experience leading to improved care. Discussion/conclusions: Key issues were highlighted, such as locating and using algorithms as an aide memoire and the limited amount of space within the dental suite. Task fixation was evident in the lead anaesthetist in trying to cannulate the patient. An intraosseous needle was placed into their hand by the operating department practitioner (ODP) using non-verbal communication. There was a good example of challenging by the recovery nurse, 'The heart rate is 50, we need to start compressions.' The simulation improved confidence and participants were keen to have simulation regularly scheduled. Recommendations: Allocation of team roles at the beginning of the session. Due to limited space, a gate keeper would be best placed to avoid overcrowding. The HALT procedure should be implemented in order to overcome communication barriers. References: Kaye Cantlay, BA MB ChB MRCP FRCA, Sean Williamson, MB ChB FRCA, Julian Hawkings, BSc BDS DGDP(UK) FDSRCPS, Anaesthesia for dentistry, Continuing Education in Anaesthesia Critical Care & Pain June 2005; 5(3):71–75. https://doi.org/10.1093/bjaceaccp/mki020 Lola Adewale, MBChB DCH FRCA, Anaesthesia for paediatric dentistry, Continuing Education in Anaesthesia Critical Care & Pain, Volume 12, Issue 6, December 2012, Pages 288–294, https://doi.org/10.1093/bjaceaccp/mks045